Antidotal Effects of the Phenothiazine Chromophore Methylene Blue Following Cyanide Intoxication. (25th March 2019) - Haouzi, Philippe; McCann, Marissa; Tubbs, Nicole; Judenherc-Haouzi, Annick; Cheung, Joseph; Bouillaud, Frederic
Abstract: Our study was aimed at (1) determining the efficacy of the dye methylene blue (MB), following a rapidly lethal cyanide (CN) intoxication in un-sedated rats; (2) clarifying some of the mechanisms responsible for the antidotal properties produced by this potent cyclic redox dye. Sixty-nine awake rats acutely intoxicated by CN (IP, KCN 7 mg/kg) received saline, MB (20 mg/kg) or hydroxocobalamin (HyCo, 150 mg/kg) when in deep coma. Survival in this model was very low, reaching 9% at 60 min without any treatment. Methylene blue significantly increased survival (59%, p  < .001) at 60 min, versus 37% with HyCo ( p  < .01). In addition, 8 urethane-anesthetized rats were exposed to a sublethal CN intoxication (KCN, 0.75 mg/kg/min IV for 4 min); they received MB (20 mg/kg, IV) or saline, 5 min after the end of CN exposure. All MB-treated rats displayed a significant reduction in hyperlactacidemia, a restoration of pyruvate/lactate ratio—a marker of NAD/NADH ratio—and an increase in CO2 production, a marker of the activity of the TCA cycle. These changes were also associated with a 2-fold increase in the pool of CN in red cells. Based on series of in vitro experiments, looking at the effects of MB on NADH, as well as the redox effects of MB on hemoglobin and cytochrome c, we hypothesize that the antidotal properties of MB can in large part be accounted for by its ability to readily restore NAD/NADH ratio and to cyclically re-oxidize then reduce the iron in hemoglobin and the electron chain complexes. All of these effects can account for the rapid antidotal properties of this dye following CN poisoning.